Stable carbon and hydrogen isotopic compositions of methane in voids from MeBo drill core GeoB23225-1 recovered from the Yam seep, Four-Way Closure Ridge, west off Taiwan (South China Sea, cruise SO266) - Thomas Pape; Janice Malnati; Gerhard Bohrmann (PANGAEA, 2024)
Carbonate core GeoB23225-1 was drilled using MARUM-MeBo200 at Four-Way Closure Ridge, South China Sea during cruise SO266/1 with R/V SONNE. Gas that has accumulated in voids in the MeBo liners was collected in order to determine stable C and H isotopic compositions of methane. Stable C and H isotopic compositions of methane were determined by use of gas chromatography-isotope ratio mass spectrometry.